Amnesia and animosity: an assessment of soccer in the States. Issue 5 (4th May 2017) - Kilpatrick, David
Abstract: The twentieth FIFA World Cup Finals, hosted by Brazil in 2014, provides perspective on the game's global growth since the inaugural tournament held in Uruguay in 1930. The fifth such tournament since the United States hosted in 1994 and the tenth in which the United States has participated, the status of the sport there remains anomalous, with compromised if not marginalized status. Elite levels of the sport, especially the Men's National Team, historically struggle for relevance in popular culture – despite widespread youth participation and the record of success achieved by the Women's National Team. This essay seeks to identify the current state of the sport in the United States as characterized by amnesia and antagonism, a conflicted blend of cultural superiority and inferiority complexes played out every four years when the nation asks itself if soccer matters.